Psychosocial Aspects During the First Wave of COVID-19 Infection in South Africa - Lentoor, Antonio G.; Maepa, Mokoena Patronella (Frontiers in Psychiatry, 2021)
Background: In South Africa, as in many countries, the nationwide spread of COVID-19 caused a public health emergency that resulted in the government implementing necessary restrictive measures such as the nationwide lockdown as a way of containing the pandemic. Such restrictive measures, while necessary, can disrupt many aspects of people’s lives resulting in unprecedented psychosocial distress. Aim: The present study aims to describe the psychosocial health and situational factors associated with the novel coronavirus (COVID-19) in South Africa during the first wave of infection. Methods: This cross-sectional survey, recruited a total of 203 participants through convenience sampling via online platforms; WhatsApp, Facebook, emails, etc. during COVID-19 lockdown in the country. Through the snowball technique, participants from across South Africa completed the online survey that assessed sociodemographic information, risk perception, history of mental health, COVID-19 related stress, and fears during the lockdown (first wave). Results: The majority of the participants who completed the survey were young, Black African, and female. Participants reported feelings of stress and anxiety (61.2%); stress about finances (39.5%); and feelings of sadness, anger, and/or frustration (31.6%) during the lockdown. Females compared to males were more likely to perceive COVID-19 as a risk to their household, X2 (20) = 45,844, p < .001 and community, X2(20) = 40,047, p = .005. COVID-19 differentially impacted the mental health of participants with and without mental health diagnoses, X2 (4) = 16.596, p = .002. Participants with a prior mental health diagnosis reported significant extra stress during lockdown (p <.05). Conclusion: The findings may be of significance to assist in the development of targeted psychosocial interventions to help people during and after the pandemic.